Anaesthetic complications in gastroschisis - Heald, Andrew (Department of Anaesthesia and Perioperative Medicine, 2025)
Introduction: Patients with gastroschisis (GS) are a vulnerable population who present to the operating theatre for pathology or central venous access related indications. Little is known about anaesthesia-related adverse events (ARAEs) in children from low- and middle-income countries (LMICs). Methods: We performed a single-centre retrospective observational study at Red Cross War Memorial Children's Hospital (RCWMCH), in Cape Town, South Africa. Data was collected from patient folders from the hospital's GS database. Each general anaesthetic exposure (GAE) was treated as an independent event and a binary logistic regression analysis was performed to assess the association between indication for GAE and the odds of an ARAE. A mixed-effects logistic regression model was used to analyse the association between adverse complications and key predictor variables in paediatric anaesthesia. Results: Seventy folders were collected between 2012 and 2021. The median gestational age was 36 weeks and median birthweight 2270g. 56 (80%) patients survived to full enteral feeds and the median duration of TPN was 18 days (IQR 12-29). There were 196 GAEs, of which pathology-related indications comprised 59%. There was a total of 94 ARAEs. At least one ARAE occurred in 79 (40%) of the 196 GAEs. Cardiovascular instability was the most common ARAE, comprising 76% of the total ARAEs. Respiratory events comprised 18% of the ARAEs, with reintubation predominating. Patients presenting for pathology related indications were associated with an unadjusted 6-fold odds increase (95% CI = 3.10, 12.27) in the odds of ARAEs compared to patients with CVC-related indications (p<0.001), however at least one ARAE occurred in 18% of CVC related GAEs. No statistically significant association with ARAE was found for gestational age, birth weight or sex. Conclusion: At RCWMCH, many patients with GS experience a complicated clinical course, requiring multiple general anaesthetic exposures. They have a high prevalence of anaesthetic related adverse events, particularly instances of CVS instability and reintubation. Establishing a multidisciplinary management protocol for these patients may decrease intervention frequency and improve outcomes.